MENINGKATKAN KEMAMPUAN BELAJAR FISIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF NUMBERED HEADS TOGETHER BERBANTUAN EDMODO - Fadila, Nurul (Prodi Teknologi Pendidikan, 2018)
Abstract. The research problem is the low level of student learning independence in learn-ing physics that have an impact on the low student learning outcomes. The purpose of this study was to find out the improvement of the independence of learning physics that has an impact on student learning outcomes using cooperative learning model of Numbered Head Together type assisted edmodo. This research use quasi-experiment design. The population in the study was all students of class X SMK N 2 Medan. The research sample consisted of 2 classes, each of which consisted of 30 students, use cluster random sampling technique. Data collection techniques for measure learning independence in form of multiple choice questionnaires totaling 15 items. Data analysis techniques used include normality test, homogeneity test, t-test, and N-gain test. The re-sults of study using the t-test obtained by tcount 4,863 while the t table was 2,002. So that t count t table (4.863 2.002) then Ha is accepted and the N-gain test shows that there is an increase in student learning independence of 0.07. From this study it can be concluded that through Edmodo assisted type Numbered Head Together cooperative learning model can increase the independence of students' physics learning.Â Abstract. Latarbelakang masalah penelitian ini adalah rendahnya tingkat kemandirian belajar siswa dalam pelajaran fisika yang berdampak pada rendahnya hasil belajar siswa. Tujuan dilakukan penelitian ini untuk mengetahui peningkatan kemandirian belajar fisika yang berdampak pada hasil belajar siswa melalui model pembelajaran kooperatif tipe Numbered Head Together berbantuan edmodo. Penelitian ini menggunakan quasi eksperiment design. Populasi dalam penelitian adalah seluruh siswa kelas X SMK Negeri 2 Medan. Sampel penelitian terdiri dari 2 kelas, yang masing-masing berjumlah 30 siswa, menggunakan teknik cluster random sampling. Teknik pengumpulan data untuk mengukur kemandirian belajar berupa kuesioner angket pilihan berganda yang berjumlah 15 item. Teknik analisis data yang digunakan meliputi uji normalitas, uji homogenitas, uji-t, dan uji N-gain. Hasil penelitian dengan menggunakan uji-t diperoleh thitung sebesar 4,863 sedangkan ttabel sebesar 2,002. Sehingga thitung ttabel (4,863 2,002) maka Ha diterima dan uji N-gain menunjukkan terdapat peningkatan kemandirian belajar siswa sebesar 0,07. Dari penelitian ini dapat disimpulkan bahwa melalui model pembelajaran kooperatif tipe Numbered Head Together berbantuan edmodo dapat meningkatkan kemandirian belajar fisika siswa.